How certain can we really be that our boss is trustworthy, and does it matter? A metacognitive perspective on employee evaluations of supervisor trustworthiness. (2nd June 2020) - Holtz, Brian C.; De Cremer, David; Hu, Biyun; Kim, Joseph; Giacalone, Robert A.
Summary: This research helps to integrate the metacognitive concept of evaluation certainty into the trust literature by demonstrating that certainty can amplify the effects of trustworthiness evaluations and stabilize trustworthiness evaluations over time. Across an experimental study (Study 1) and a multiwave survey of employees (Study 2), we show that trustworthiness evaluations exert a stronger influence on individuals' trust at higher levels of certainty and that trust transmits the multiplicative effects of trustworthiness evaluations and certainty on key indicators of employee risk‐taking including reliance and disclosure behavior. Further, in Study 2, we show that certainty can help predict change in trustworthiness evaluations over time. Finally, in a two‐wave field survey (Study 3), we examine factors that influence evaluation certainty and show that relational transparency and leader prototypicality (LP) have interactive effects on employees' certainty such that the influence of relational transparency on certainty will be more positive at higher levels of LP. Theoretical and practical implications are discussed.